The Role of Executors in Mariage Properties Sharing Based on Islamic Law - Syuaib Syuaib; M. Taufan B.; Ermawati Ermawati (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
This study discusses the duties and functions of court bailiff in the settlement of marriage properties or gono gini in the religion court. This study used qualitative method which the data were collected through direct observation and interviews with the religious court staff and judges. The findings show that the tasks and roles of the bailiff at the religious court in solving the marriage properties. They play an important role in carrying out the execution of the marriage properties ot gono gini ssets. In the process of confiscation of the marriage properties, the confiscator is an important component in the final stage of the settlement of a case. The steps or stages of the process of carrying out the confiscation of the bailiffs are waiting for the verdict issued by the head of the judges in the settlement of marriage properties. Importance prospects of thought to the question of duty and fun g of the bailiff to the people as possible with their special studies were made of the court to the public.